2001
DOI: 10.1021/jp003490q
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Mechanistic Studies of the Chemical Vapor Deposition of Tungsten Nitride from Bis(Tertbutylimido)Bis(Tertbutylamido)Tungsten

Abstract: The chemical vapor deposition (CVD) of tungsten nitride from a single source reagent, bis(tertbutylimido)bis(tertbutylamido)tungsten ((t-BuN)2W(NHBu-t)2), is examined with particular focus placed on the mechanisms and energetics involved in the activation and thermal decomposition of this CVD precursor. The main reactions that take place are (1) activated adsorption of the precursor, (2) hydrogen addition/exchange, leading to the evolution of tert-butylamine, (3) ligand activation via both γ-hydride activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Previous studies have shown that the tert-butyl groups of the tert-butylimido ligand liberated isobutylene through a c-hydrogen elimination process. [16][17][18] We speculate that the source of the carbide atoms is more likely to be from the neopentyl ligands, [4][5][6][7][8][9][10][11][12] generated via the pathways shown in Scheme 1 discussed above.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the tert-butyl groups of the tert-butylimido ligand liberated isobutylene through a c-hydrogen elimination process. [16][17][18] We speculate that the source of the carbide atoms is more likely to be from the neopentyl ligands, [4][5][6][7][8][9][10][11][12] generated via the pathways shown in Scheme 1 discussed above.…”
Section: Resultsmentioning
confidence: 99%
“…Deposition of nitride thin films has been reported employing metal complexes with organo-amido and organo-imido ligands as the precursors. [13][14][15][16][17][18][19] These include the deposition of nitrides of Ti from Ti(NEt 2 ) 4 , [13][14][15] of Ta from t BuNLTa(NEt 2 ) 3 , 16 and of W from ( t BuNL) 2 W(NH t Bu) 2 . 17,18 In addition to the activation and elimination pathways of the hydrocarbon fragments of the complexes, the role of the multiply bonded carbene, carbyne and imido ligands are frequently discussed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• C) [15][16][17][18][19][20][21][22] that can compromise contact level structures 2,23 and neighboring dielectrics. 24 In addition, the development of ultra-low temperature CVD WN x C y has potential application to flexible and organic devices.…”
mentioning
confidence: 99%
“…Typically, refractory metal nitride diffusion barriers show decreasing N levels with increasing deposition temperature due to N 2 desorption. [29][30][31][32] Films deposited at 300 C show greater than 20 atom % O, but decreased significantly to 14 atom % at 450 C. As the deposition temperature increased from 450 to 700 C, the O level decreased gradually to 5 atom %. A decrease in the O levels at higher deposition temperature is consistent with the increase in grain size because oxygen is introduced into the film by post-growth diffusion.…”
Section: Resultsmentioning
confidence: 99%